2020
DOI: 10.18488/journal.82.2020.71.1.11
|View full text |Cite
|
Sign up to set email alerts
|

An Assymetric Evaluation of Oil Price- Inflation Nexus: Evidence from Nigeria

Abstract: This paper investigates the asymmetric oil price-inflation nexus in Nigeria covering the period of 2009Q1 and 2018Q4. We adopt the Nonlinear Autoregressive Distributed Lags (NARDL) model approach. The result of the study indicates that there exists a nonlinear long run connection between international oil price and inflation in Nigeria which suggests that fluctuations in oil price influence domestic inflation in Nigeria asymmetrically. Further, the result of the study indicates that in the long run, both incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The relationship between commodity prices and inflation is complex and varies across different countries and periods. In Nigeria, fluctuations in oil prices asymmetrically influence domestic inflation, with both increases and decreases in oil prices leading to a decline in inflation [24]. In Saudi Arabia, there is a dynamic nexus between oil prices, the Saudi/US dollar exchange rate, inflation, and output growth rate [25].…”
Section: Commodity Prices (Cocoa Oil Gold Petrol Diesel) and Inflatio...mentioning
confidence: 99%
“…The relationship between commodity prices and inflation is complex and varies across different countries and periods. In Nigeria, fluctuations in oil prices asymmetrically influence domestic inflation, with both increases and decreases in oil prices leading to a decline in inflation [24]. In Saudi Arabia, there is a dynamic nexus between oil prices, the Saudi/US dollar exchange rate, inflation, and output growth rate [25].…”
Section: Commodity Prices (Cocoa Oil Gold Petrol Diesel) and Inflatio...mentioning
confidence: 99%
“…Conversely, Nasir et al (2023) posited that negative shocks to oil prices had a greater impact than positive shocks of comparable magnitude on domestic inflation in Nigeria. Alimi et al (2020) applied the NARDL modelling approach to assess the asymmetric influence of oil prices on inflation in Nigeria. Their study not only confirmed the asymmetric impact of oil prices on domestic inflation but also affirmed that oil price shocks had a long-term negative effect on domestic inflation.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…Alimi et al. (2020) applied the NARDL modelling approach to assess the asymmetric influence of oil prices on inflation in Nigeria. Their study not only confirmed the asymmetric impact of oil prices on domestic inflation but also affirmed that oil price shocks had a long‐term negative effect on domestic inflation.…”
Section: Literature Reviewmentioning
confidence: 99%